Adjustable book end (ABE) - Zakaria, Mohd Hazare; Othman, Sasmin; Moohd Noh, Mohd Razif; Nordin, Mohd Fadzly Ryza; Mohd Lutfi, Muhammad Farizulazman (Universiti Teknologi MARA, Kedah, 2019)
This Adjustable Book End (ABE) is categorized as a refinement innovation, which is an innovation idea inherent to the manual book organization system. With the ABE the work of book preparation will be systematic and organized. Implementing ABE can help the department adopt a more efficient adjustable bookcase tool for more efficient and orderly book preparation. As such, books on the shelves will look neat at all times without the supervision of the staff. With the implementation of the ABE at Kedah State Library (PPAK), the condition of the books on the shelves is neatly organized, neat and orderly to attract users to the library. This has led to increased reading among the people of the state due to the easy search of materials on the shelves. The conducive infrastructure will attract users to continue using the library service. As such, it improves library membership, service quality and departmental image. It also creates a proactive and culturally minded first-class community. Implementation of the project has had a significant and positive impact on customers, increased efficiency and optimized costs in addressing financial and human resource constraints, leveraging on new technology capabilities and introducing new service delivery approaches to PPAK staff and users.